Financial accounting : a decision-making approach - King, Thomas E.; Lembke, Valdean C.; Smith, John H. (New York : John Wiley, 2001)
Business
2004-05-05
Keywords: Financial accounting; Capital markets; Financial auditing; Revenue forecasts